Dapur Sehat Atasi Stunting (DAHSAT) Solusi dalam Menekan Jumlah Stunting di Desa Bandarjo Kabupaten Semarang - Khairun Nisa Puspita Ningrum (Universitas Negeri Semarang, 2026)
Community service through the Community Service Program (KKN) is a form of student contribution in overcoming problems in the community. The Healthy Kitchen to Overcome Stunting (DASHAT) program in Bandarjo Village is one of the effective solutions to reduce stunting by using affordable local food ingredients. This program aims to examine the role of KKN in providing education to improve the quality of community nutrition through education and the provision of healthy food based on local food sources that are easily accessible in Bandarjo Village, Semarang Regency. The DASHAT program is aimed at pregnant women, nursing mothers, and families at risk of stunting by providing intensive training on how to prepare healthy, nutritious, and affordable food. In addition, DASHAT also seeks to ensure that the nutritional needs of families are well met, thereby improving the overall welfare of the community in the Bandarjo, West Ungaran area. The expected results after this program include improved community welfare and increased awareness regarding the importance of meeting family nutritional needs. By doing so, Bandarjo Village is expected to significantly